PENGELOLAAN KEGIATAN BUDIDAYA RUMPUT LAUT OLEH PEMBUDIDAYA DI PERAIRAN LABUHAN SANGORO, TELUK SALEH, KABUPATEN SUMBAWA - Baiq Hilda Astriana; Aryan Perdana Putra (Universitas Mataram, 2024)
West Nusa Tenggara (NTB) is one of the largest seaweed producers in Indonesia. Seaweed farming locations can be found in Lombok Island and Sumbawa Island waters. This activity has become one of the livelihoods, even the main livelihood for coastal communities. Apart from that, the NTB government is also encouraging the development of seaweed production through PIJAR (cattle, corn and seaweed) program. Saleh Bay, as one of the bays known as a megabiodiversity area, has long been used as an area for seaweed farming activities. However, recently, there have been problems related to seaweed diseases causing losses for farmers. To be precise, significant cases of this disease appeared in one of the waters in Saleh Bay, namely the waters of Labuhan Sangoro. Various predictions have emerged regarding the seaweed disease. However, it cannot be confirmed precisely. Therefore, a research regarding seaweed cultivation management by farmers in Labuhan Sangoro needs to be conducted. The method used in this research was interview using a questionnaire (primary data). Respondents were selected purposively. Those selected were seaweed farmers and the number of respondents was as many as farmers who were still actively cultivating seaweed. The data obtained was then analyzed descriptively and qualitatively. The result of this research shows that respondents have good knowledge in managing seaweed seaweed farming, and have a tendency to continue carrying out seaweed farming even though there are some obstacles they often face related to financial and natural factors. However, education is still needed regarding the potential causes of seaweed diseases and efforts to treat them.